The Impact of Larung Sesaji Traditional Culture Modification in Tambakrejo Village - Mellina, Zulvida Maya Rizqi; Purwasih, Joan Hesti Gita; Hadi, Nur (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2022)
Degraded existence of a tradition is due to 3 (three) main factors: inadequate knowledge on objective and meaning of tradition, inadequate contribution of community and lack of novelty in tradition. Considering such conditions, the author tries to raise the change and the impact of tradition on community life. The author used qualitative method with ethnographic research approach. Techniques of collecting data used were observation, interview, and documentation. The result of research shows the implementation process and the objective of tradition to document culture in order to be preserved in the future. Meanwhile, technique of analyzing used in this research is social construction perspective suggested by Peter L Berger &Luckmann to explain data found. The finding of research indicates that tradition changes with time and affects Tambakrejo people. Public participation is needed to maintain the tradition sustainability. Therefore, to preserve larung sesaji tradition, good human resource, innovation, and creativity are required to face the challenge of tradition existence in the future.